1992
DOI: 10.1002/art.1780350614
|View full text |Cite
|
Sign up to set email alerts
|

Anticentromere antibody as a predictor of digital ischemic loss in patients with systemic sclerosis

Abstract: Objective. To determine the clinical and serologic risk factors for digital ischemic events in patients with systemic sclerosis (SSc).Methods. Systemic sclerosis (SSc; scleroderma) is a heterogenous disorder with a variable course and out-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 25 publications
5
61
2
5
Order By: Relevance
“…Anticentromere autoantibodies are most often found in patients with l-SSc who will most likely develop advanced Raynaud's phenomenon, PAH, and digital ulcers [14], whereas antiScl-70 autoantibodies are associated with d-SSc patients who are likely to develop diffuse cutaneous disease and pulmonary fibrosis [6].…”
Section: Autoantibodies To Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticentromere autoantibodies are most often found in patients with l-SSc who will most likely develop advanced Raynaud's phenomenon, PAH, and digital ulcers [14], whereas antiScl-70 autoantibodies are associated with d-SSc patients who are likely to develop diffuse cutaneous disease and pulmonary fibrosis [6].…”
Section: Autoantibodies To Endothelial Cellsmentioning
confidence: 99%
“…SSc patients with limited cutaneous disease frequently develop extreme tissue ischemia that results in ischemic digital loss (IDL) [14]. To examine the possibility that the two autoantigens cleaved exclusively by granzyme B-CENP-B and fibrillin-may be associated with IDL, HeLa cell lysates and chromosome preparations were incubated with or without granzyme B and then immunoblotted with sera from patients with limited SSc and IDL or limited SSc and no IDL.…”
Section: Autoantibodies To Endothelial Cellsmentioning
confidence: 99%
“…[2] Out of two prospective cohort studies in UK , one study found that 28 (16%) of 171 SSc patients had at least one digital amputation and 73 (43%) had experienced at least one episode of severe digital ischemia, [3, and in another study 17.4% were found to have complications related to severe digital vasculopathy including digital ulcers, critical digital ischemia, gangrene, or the need for digital sympathectomy. Furthermore, 1.6% of the total cohort developed critical digital ischemia, 1.4% developed digital gangrene, and 0.9% required amputation.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of patients at one center reported that younger patients with high Rodnan skin score were at higher risk for developing ulcers, and they usually occurred within 5 years of non-Raynaud's symptoms [10]. Digital amputation secondary to occlusion of digital arteries occur in a subset of (11%) patients, usually with limited skin disease with the presence of anticentromere antibody [11][12][13].…”
Section: Raynaud's Phenomenonmentioning
confidence: 99%
“…In scleroderma patients, anticentromere antibodies have been significantly associated with thrombotic manifestations such as digital ischemia [226], and antiendothelial cell antibodies have been found that bind to centromeric protein B [227]. This suggests that antiendothelial antibodies target nonendothelial cell specific antigens.…”
Section: Antiendothelial Cell Antibodiesmentioning
confidence: 99%